Anomalous Photodeposition of Ag on Ferroelectric Surfaces with Below‐Bandgap Excitation. Issue 3 (21st January 2014) - Seal, Katyayani; Rodriguez, Brian J.; Ivanov, Ilia N.; Kalinin, Sergei V.
<x xml:space="preserve">Abstract</x> Ferroelectric lithography, a recent method of fabricating functional interfaces, traditionally involves photoreduction on polarized ferroelectric surfaces at optical energies above the bandgap of the ferroelectric. In this work, for the first time, photochemical deposition of elemental Ag nanoparticles on a specifically poled lithium niobate substrate is reported, with a broad white‐light spectrum transmitted through the crystal. The transmitted light has energies only below the bandgap, leading to the conclusion that the Ag reduction proceeds through non‐linear effects, specifically, second harmonic generation.